«Horses also Flew as Birds […]». Animal Analogies in Kraszewski’s Literary Works - Penińska, Małgorzata (The Motifs of Fauna and Flora in Literature and Culture, 2018)
The paper presents animal analogies in Kraszewski’s literary works. The analysis of the data is to display stereotypical and authentic analogy. The base of analogy is observation of life and attitudes among the animals. The analogy gives knowledge about the people and fussy information about animals.